Preventing cyberbullying through ICT-centric education: a case study - Said-Hung, Elías Manuel; Gonzalez-Prieto, E.; Pallarés Piquer, Marc (Routledge, 2022)
Numerous studies have examined the phenomenon of bullying. The development of information and communications technology (ICT) has enabled an emerging form of bullying known as cyberbullying. This article presents a case study of an Internet-focused bullying prevention programme in a Spanish secondary school with 627 students, from a non-experimental, qualitative perspective. The data collected show an ICT-centric institutional framework that supports bullying prevention programmes. The results also indicate an institutional culture highly adapted to ICT based on teleological, psycho-pedagogical, administrative and community dimensions. This culture has favoured the development of the cyberbullying prevention programme studied in this article. © 2021 Technology, Pedagogy and Education Association.
Keywords: cyberbullying; ICT; institutional culture; prevention programme; violence in schools; Scopus; JCR